Consequences of inconsistently classifying woodland birds - Fraser, Hannah; Garrard, Georgia E.; Rumpff, Libby; Hauser, Cindy E.; McCarthy, Michael A. (Frontiers in Ecology and Evolution, 2015)
There is a longstanding debate regarding the need for ecology to develop consistent terminology. On one hand, consistent terminology would aid in synthesizing results between studies and ease communication of results. On the other hand, there is no proof that standardizing terminology is necessary and it could limit the scope of research in certain fields. This article is the first to provide evidence that terminology can influence results of ecological studies. We find that researchers are classifying ‘woodland birds’ inconsistently because of their research aims and linguistic uncertainty. Importantly, we show that these inconsistencies introduce a systematic bias to results. We argue that using inconsistent terms can bias the results of studies, thereby harming the field of ecology, because scientific progress relies on the ability to synthesize information from multiple studies.